Thorndike Theory and It’s Application in Learning - Muhammad Hifdil Islam (At- Ta'lim : Jurnal Pendidikan, 2015)
This article will explain one of theories in learning; that is theory of Thorndike. This theory is developed by education psychology experts from America whose name Edward Lee Thorndike, (Next will be mentioned as Thorndike). Thorndike was born in Wiliamsburg on 31 August 1874 and died in Montrose, New York, on 10 August 1949. He is prominent figure from Fungsionalism ideology of Columbia. After finished his study in Harvard University, he works in Teacher’s College of Columbia under lead of James Mckeen Cattell. Here, his passion to learning process, education and intelligences. On 1898, in his 24 ages, Thorndike publisehed his own books entitled Animal Intelligence, An Experimental Study of Association Process in Animal. Thorndike has profession as an educator and Psychologist. Graduated from his first strata form Wesleyen University in Conecticut on 1895, second strata from Harvard on 1896 and seize his doctor degree in Colombia on 1898. He published some books such as: Educational Psychology (1903), Mental and social Measurements (1904), Animal Intelligence (1911), A teacher’s Word Book (1921),Your City (1939), dan Human Nature and The Social Order (1940) . And it will explain such as: Explaining law of learning based on Thorndike, explaining how learning principle of Thorndike in learning process, explaining application of Thorndike theory in learning, and giving an analysis to Thorndike theory 1